BEHAVIOR OF HOUSEHOLD WASTE MANAGEMENT - Henni Febriawati; Wulan Angraini; Ivan Ahmad Nurcholis; Sarkawi (Poltekkes Kemenkes Bengkulu, 2023)
Bengkulu province experiences an annual accumulation of waste amounting to 38,417.16 tons. The issue of garbage is not something to be taken lightly as it concerns the livelihoods of many people. Practically all waste management leads to landfills, imposing a tremendous burden on these waste disposal sites. It requires not only extensive land but also expensive environmental protection facilities. The increasing volume of waste being sent to the landfill is one of the reasons why there hasn't been a concerted effort to reduce the amount of waste at its source. The aim is to understand the factors that influence household waste management behavior. This study employed a community-based approach with a cross-sectional research design conducted in June and July 2023. The study's population consists of households in the city of Bengkulu in the year 2021. A sample of 542 households was chosen using the simple random sampling method. This study has received an ethical clearance certificate from Bengkulu Health Polytechnic with Reference No. KEPK.BKL/416/06/2023 dated June 30, 2023. The data analysis involves univariate and bivariate analysis, including the chi-square test. The majority of households in Bengkulu City are aged between 29 and 58 years old. They are mostly married, have educational levels below high school, are unemployed, possess limited household knowledge, exhibit a less favorable attitude, and most households demonstrate insufficient behavior regarding household waste management. Age, marital status, education, and occupation show no correlation with behavior in household waste management. There is a relationship between knowledge and attitude with behavior in household waste management. Households with limited knowledge are at an 8.4 times higher risk of displaying insufficient behavior in waste management. Additionally, households with inadequate knowledge face a 8.94 times higher risk of demonstrating deficient behavior in waste management. Regular education-based socialization and accompanying support in waste management can serve as an alternative to enhance households' knowledge and attitude towards waste management. Providing facilities and infrastructure support, such as composters or biopores for organic waste management, as well as offering training on the utilization of inorganic waste, can be a solution to transform community behavior regarding waste management. This will ultimately lead to th